Analysis of Reinforced Concrete Structures for Accidental Blast during Launching of a Rocket - Lovepreet SINGH; Nirmal Rakeshbhai RAVALIYA; M. Abdul AKBAR (INCAS Bulletin, 2021)
Despite the greatest efforts, accidents continue to happen during the process of rocket launching, either in the form of generated blast wave or the debris that flies and hits random objects. In this paper, the impact of blast loading created by a rocket launch on the tie connection and the three-hinged arch is studied using the finite element model in ABAQUS. The impact of rocket launching was modelled using the physical characteristics/geometry of the launch pad, and a blast load intensity equivalent to 20,000lbs of TNT is applied using the CONWEP module. The tie connection and three-hinged arch after validation and mesh convergence study are applied with service loads in concurrence with the blast loading. The additional impact of blast loads on the static and dynamic response of the structure is studied. The distance of the structures from the point of blast (rocket launching site) is varied, and parametric studies are carried out to arrive at detailed guidelines on the minimum safety distance that stand-alone civil infrastructure should follow in order to minimize the rocket launching impact.